Letter (copy) : Spanish seamen - Tewson, Vincent
1940-07-31 025a-0028-002 International. HVT/AC/DT/1206. 31st July, 1940. Captain W. H. Coombs, The Navigators and Engineer Officers' Union, 23 Leadenhall Street, LONDON.E.C.3. Dear Captain Coombs, SPANISH SEAMEN. I have your letter of the 25th of July and quite understand the difficult position in which the International Mercantile Marine Officials Association finds itself because of the very considerable calls which have been made recently on its finances, with the result that it is unable to make a further donation of £20 to tne Spanish Seamen's Fund on this occasion. 292/946/25a/28(ii)